The Role of Corporate Governance in Achieving SDGs among Malaysian Companies - Buniamin, Sharifah; Jaffar, Romlah; Ahmad, Norkhazimah; Johari, Nor Hasimah (European Journal of Sustainable Development, 2022)
While the Sustainable Development Goals (SDGs) agenda is applicable to the member states of the UN, many other players are also involved, such as corporations. The primary and economic value chain activities and aims of major companies mean they will ultimately have a crucial and explicit role to play in enabling the SDGs to be attained. In Malaysia, there have been few studies on firms’ engagement in reaching the SDGs. Therefore, the current study aimed to examine the roles played by corporations in enabling SDGs to be attained. A specific analysis was conducted to determine if a company’s participation in the SDGs can be influenced by first-rate corporate governance. The data was collected using content analysis of 87 corporate annual reports of public listed companies from Malaysia. The boards’ independence, size, meeting frequency, and gender diversity were the corporate governance practices examined. An annual report may include details of the company’s role in the SDGs as a proxy for the corporate’s SDG involvement. The findings shed light on the nature of business involvement in the SDGs. The SGD with the most frequent reporting was Goal 8 - Decent work and economic growth, while the SDG with the most frequent reporting was Goal 2 - Zero Hunger. These results indicate that a company’s SDG participation has a positive relationship with certain governance practices of corporations, especially the board meeting frequency. Moreover, these results may serve to emphasise to regulators and policymakers that all corporations require effectual corporate governance so that the challenges facing the world and its population every day can be addressed, leading to an improved and more sustainable future for everyone. Keywords Sustainable Development Goals (SDGs), corporate governance, Malaysia, companies, content analysis